Prognostic Value of Tumor-Stroma Ratio in Rectal Cancer: A Systematic Review and Meta-analysis - Zhu, Yuzhou; Jin, Zechuan; Qian, Yuran; Shen, Yu; Wang, Ziqiang (Frontiers in Oncology, 2021)
Background: Tumor-stroma ratio (TSR) is a promising new prognostic predictor for patients with rectal cancer (RC). Although several studies focused on this pathologic feature, results from those studies were still inconsistent. Methods: This research aimed to estimate the prognostic values of TSR for RC. A search of PubMed, EMBASE, and Web of Science was carried out. A meta-analysis was performed on disease-free survival, cancer-specific survival, and overall survival in patients with RC. Results: The literature search generated 1,072 possible studies, of which a total of 15 studies, involving a total of 5408 patients, were eventually included in the meta-analysis. Thirteen of the 15 articles set the cut-off for the ratio of stroma at 50%, dividing patients into low-stroma and high-stroma groups. Low TSR (rich-stroma) was significantly associated with poorer survival outcome. (DFS: HR 1.54, 95% CI 1.32-1.79; OS: HR 1.52 95% CI 1.34-1.73; CSS: HR 2.05 95% CI 1.52-2.77). Conclusion: Present data support TSR to be a risk predictor for poor pronosis in RC patients.